Studies on the Involvement of the Exopolysaccharide Produced by Cystic Fibrosis-Associated Isolates of the Burkholderia cepacia Complex in Biofilm Formation and in Persistence of Respiratory Infections - Cunha, Mónica V. (American Society for Microbiology, 2004)
Bacteria belonging to the Burkholderia cepacia complex (BCC) are important opportunistic pathogens that lead to respiratory infections in patients with cystic fibrosis (CF). The clinical outcome following colonization with BCC bacteria is highly variable, and so far, unpredictable. A large percentage (80 to 90%) of BCC isolates from CF patients produce the exopolysaccharide (EPS) cepacian, which has been hypothesized to play a role in the colonization and persistence of these bacteria in the CF lung. In this work, we demonstrate that although it is not required for the initiation of biofilm formation, cepacian plays a role in the establishment of thick biofilms. This conclusion was based on a comparison of the abilities of EPS-defective mutants derived from a B. cepacia mucoid CF isolate by random plasposon insertion mutagenesis and the ability of the parental strain to form biofilms. However, the systematic characterization of 108 CF isolates, corresponding to 15 distinct strains, indicated that other strain-dependent factors are also involved in the development of thick, mature biofilms. The isolates examined belonged to the species B. cepacia, B. multivorans, B. cenocepacia, and B. stabilis and were obtained during a 7-year period of surveillance from 21 CF patients receiving care at the major Portuguese CF center. Most of them (90%) were serial isolates from 12 persistently infected patients. In spite of the concept that bacteria growing in biofilms display more resistance to antibiotics and to host phagocyte killing than do planktonically growing cells, no clear correlation could be established between the ability of the various strains examined to produce EPS and/or to form biofilms in vitro and the persistence or virulence of the respiratory infections they caused in different patients.